Problems That Teachers Coincide with in Physical Education Lessons Who Changed Classroom Teaching Branch to Physical Education Teaching - Mehtap Yıldız; Özer Yıldız (Türk Spor ve Egzersiz Dergisi)
ABSTRACTThe purpose of this study is to determine the problems faced by teachers in physical education lessons who pass from classroom teaching to physical education teaching. Interview technique, which is one of the qualitative research methods, was used in the research. The research group consisted of teachers who passed from physical education teaching to physical education teaching branch and working in various districts of Konya in the 2018-2019 Academic Year (n = 12 male, n = 1 female). “Personal Information Form” and semi-structured “Interview Form” developed by the researchers were used as data collection tools. The data were evaluated by content analysis method. As a result of the research, it was found out that classroom teachers who had to pass to physical education teaching by changing the field had to deal with many problems.